Functional assessment of lysosomal Rab7 and RILP with RNA interference and overexpression in Spodoptera frugiperda Sf9 cell lines - Cui, Gaofeng; Jiang, Zhiyan; Zhong, Guohua (STAR protocols, 2023)
The interaction manner and biological function of Rab7 and its effector, Rab-interacting lysosomal protein (RILP), remain unclear in invertebrates. We provide a protocol for detecting the effects of Rab7 and RILP terminals on lysosome and autophagy in Spodoptera frugiperda Sf9 cells with overexpression and RNA interference. We describe steps for overexpressing plasmids, generating long double-stranded RNA, and transfecting them into Sf9 cells. We then detail procedures for cell immunofluorescence imaging with harmine treatment and fluorescence analysis. For complete details on the use and execution of this protocol, please refer to Cui et al. (2023).1 [Display omitted] •Construct insect lysosomal Rab7/RILP overexpression plasmids for fluorescence analysis•RNA interference of Rab7 and RILP to reveal the influence on lysosome and autophagy•Explore biological role of Rab7-RILP interaction via cell immunofluorescence Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The interaction manner and biological function of Rab7 and its effector, Rab-interacting lysosomal protein (RILP), remain unclear in invertebrates. We provide a protocol for detecting the effects of Rab7 and RILP terminals on lysosome and autophagy in Spodoptera frugiperda Sf9 cells with overexpression and RNA interference. We describe steps for overexpressing plasmids, generating long double-stranded RNA, and transfecting them into Sf9 cells. We then detail procedures for cell immunofluorescence imaging with harmine treatment and fluorescence analysis.